Determining a national nomenclature: creative ascendancy in Lesotho literature in English - Viriri-Shava, Piniel; Nyawo-Viriri-Shava, Vongai (Social Science Consultancy Trust, 2016)
Historically, the emergency and evolution of literature in Lesotho has been closely linked to the Evangelical mission of the church and the dominance of Sesotho as sole linguistic vehicle for communication and creative imagination. This scenario has meant that for years, literature written in the vernacular-Sesotho-has tended to take pride of place at the expense of literary writing in English or any other language.